2003
DOI: 10.1093/humrep/deg277
|View full text |Cite
|
Sign up to set email alerts
|

Electro-acupuncture as a peroperative analgesic method and its effects on implantation rate and neuropeptide Y concentrations in follicular fluid

Abstract: EA does not improve pregnancy rate in the present clinical situation. The observation that NPY concentrations in FF were higher in the EA group may be important for human ovarian steroidogenesis. The analgesic effects produced by EA are as good as those produced by conventional analgesics, and the use of opiate analgesics with EA is lower than when conventional analgesics alone are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 27 publications
3
68
0
4
Order By: Relevance
“…Other study showed that acupuncture had comparable analgesic effect as conventional analgesia. Similar results on the analgesic effect of acupuncture were subsequently reported by the same group (Stener-Victorin et al, 2003). Acupuncture can be recommended as one of the effective analgesic methods for patients who are unable to comply with the conventional analgesia because of adverse effects during and after transvaginal ultrasound-guided oocyte retrieval (Sator-Katzenschlager et al, 2006).…”
Section: Introductionsupporting
confidence: 60%
“…Other study showed that acupuncture had comparable analgesic effect as conventional analgesia. Similar results on the analgesic effect of acupuncture were subsequently reported by the same group (Stener-Victorin et al, 2003). Acupuncture can be recommended as one of the effective analgesic methods for patients who are unable to comply with the conventional analgesia because of adverse effects during and after transvaginal ultrasound-guided oocyte retrieval (Sator-Katzenschlager et al, 2006).…”
Section: Introductionsupporting
confidence: 60%
“…NPY is supposed to play important roles in regulating ovarian functions, follicular growth and ovulation. A prospective, randomized and multicentre clinical trial including 286 patients undergoing IVF treatment found electro-acupuncture significantly increased the levels of NPY in follicular fluids, which may be important for human ovarian steroidogenesis 53 . TGF-alpha, as a 50 amino acid polypeptide present predominantly in theca cells of antral follicle, has been found to regulate the growth of follicles 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies to evaluate both the pain relieving effect of electroacupuncture (EA) during oocyte aspiration and the effect of EA on the number of pregnancies have been published. [139][140][141][142] EA was found to induce pain relief similar to that induced by a fast acting opioid during oocyte retrieval and to have fewer negative side effects. [142][143] Also, the results suggest that acupuncture may have a positive effect and no adverse effects on pregnancy outcome.…”
Section: Assisted Reproductive Technologymentioning
confidence: 95%